2010
DOI: 10.2174/138920010791110836
|View full text |Cite
|
Sign up to set email alerts
|

Nanocarriers: A General Strategy for Enhancement of Oral Bioavailability of Poorly Absorbed or Pre-Systemically Metabolized Drugs

Abstract: Oral delivery remains the preferred route for chronic drug administration thanks to its patient convenience and compliance. However, many drug candidates are unsuitable for conventional oral formulations due to low solubility, poor membrane permeability, or extensive pre-systemic metabolism. This review describes a promising strategy that incorporates or encapsulates the molecules with biodegradable and biocompatible nanoparticulate carriers. The entrapped drug substances can be protected against degradation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(44 citation statements)
references
References 0 publications
2
41
0
1
Order By: Relevance
“…It has been well accepted that particle size is a critical parameter to be controlled, in that it might play a key role in determining the fate of nanocarriers after oral administration (Cai et al, 2010 (DLS) measurement revealed that the mean particle size of two silybin-loaded micelles was around 130 nm and the size distribution was in the range of 60.3-269.7 nm. Therefore, silybin-loaded micelles might be transported in the small intestine by multiple pathways including endocytosis by enterocytes and M cells.…”
Section: Characterization Of Silybin-loaded Micellesmentioning
confidence: 99%
“…It has been well accepted that particle size is a critical parameter to be controlled, in that it might play a key role in determining the fate of nanocarriers after oral administration (Cai et al, 2010 (DLS) measurement revealed that the mean particle size of two silybin-loaded micelles was around 130 nm and the size distribution was in the range of 60.3-269.7 nm. Therefore, silybin-loaded micelles might be transported in the small intestine by multiple pathways including endocytosis by enterocytes and M cells.…”
Section: Characterization Of Silybin-loaded Micellesmentioning
confidence: 99%
“…Several approaches have been applied in order to improve the oral bioavailability of poorly permeable and soluble compounds intended for oral administration. Using nanoparticulate drug delivery system is considered as one of these strategies (Cai et al, 2010;Saha et al, 2010). These formulations have been shown to be efficient approaches to enhance the transport of a large number of drugs including nucleic acids and genes across many biological membranes as well as to improve the stability of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…One of the reasons pointed as the basis of this decision is the fact that nanoparticle uptake by intestinal cells has been reported several times, either by the M-cells located in the Peyer's patches (Borges et al, 2006, Pinto Reis et , 2006) or by the enterocytes, benefiting from transcellular and paracellular transport (Cai et al, 2010, Pinto Reis et al, 2006. A first study revealed that, after oral delivery to mice of alginate nanoparticles containing the three drugs mentioned above plus etambutol, plasma drug levels were detected during 7-13 days.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%